Empowering special property development entity (SPDE) for waqf land development / Dr. Ahmad Shazrin Mohamed Azmi, Prof. Dr. Noor Rosly Hanif and Assoc. Prof. Dr. Siti Mashitoh Mahamood - Mohamed Azmi, Ahmad Shazrin; Hanif, Noor Rosly; Mahamood, Siti Mashitoh (College of Built Environment, 2023)
The Special Property Development Entity (SPDE) is a structurally subsidiary of SIRCs, waqf governing agency or any related organisation.